Atypical Intraepidermal Melanocytic Proliferation Masked by a Tattoo: Implications for Tattoo Artists and Public Health Campaigns - Navrazhina, Kristina (Cureus, 2018)
Tattoos have become increasingly popular worldwide. While tattoos carry a minimal risk of complications, previous reports have located malignant melanoma hidden within tattoos. We present a case of an atypical intraepidermal melanocytic proliferation masked by a large tattoo in a 39-year-old Caucasian male. Tattooed skin can be difficult to examine, particularly when the tattoos are dark, pigmented, and extensive. We demonstrate that a careful examination of tattooed skin leads to the early detection of atypical melanocytic proliferations. We present an extensive review of literature related to the relationship between tattoos and skin cancer, as well as public health recommendations for tattoo artists and individuals seeking to obtain tattoos. We urge a vigilant examination of tattooed skin and encourage collaboration between dermatologists and tattoo artists in promoting the detection of suspicious lesions prior and following tattooing.